Niche Inheritance: A Cooperative Pathway to Enhance Cancer Cell Fitness Though Ecosystem Engineering. Issue 9 (September 2014) - Yang, Kimberline R; Mooney, Steven M.; Zarif, Jelani C.; Coffey, Donald S.; Taichman, Russell S.; Pienta, Kenneth J.
Abstract Cancer cells can be described as an invasive species that is able to establish itself in a new environment. The concept of niche construction can be utilized to describe the process by which cancer cells terraform their environment, thereby engineering an ecosystem that promotes the genetic fitness of the species. Ecological dispersion theory can then be utilized to describe and model the steps and barriers involved in a successful diaspora as the cancer cells leave the original host organ and migrate to new host organs to successfully establish a new metastatic community. These ecological concepts can be further utilized to define new diagnostic and therapeutic areas for lethal cancers. 115: 1478–1485, 2014. © 2014 Wiley Periodicals, Inc.